Effect of Track Support Structures on Friction-Induced Vibrations of Wheelset-Track Systems - Fu, Hua; Kang, Fei; Liu, Shanglin; Kang, Xi (Shock and Vibration, 2023)
The aim of the present investigation is to study the effect of track support structures on the metro 5th to 8th-order out-of-round (OOR) wheel caused by friction-induced vibrations. Three finite element models of metro-leading wheelset-track systems with three types of track support structures were established. The motion stabilities of these systems were studied using the complex feature value method. Three unstable vibrations that may cause the formation of the 5th to 8th order wheel OOR profiles were predicted. The simulation results show that the saturated creep forces can lead to unstable vibrations of wheelset-track systems, which are capable of inducing the 5th to 8th-order OOR wheel shapes. Choosing the appropriate value of the fastener damping and using the rail dampers are helpful to reduce or even eliminate wheel polygonal wear caused by these vibrations.